Akibat Hukum Bagi Nasabah Terhadap Pelaksanaan Merger Badan Usaha Perbankan di Indonesia - Widyantoro, Agus; Putri, Dita Elvia Kusuma (Acten Journal Law Review, 2025)
Limited Liability Companies as legal entities can operate in the banking sector. In its development, many companies have merged in the banking industry to increase activity and respond to economic conditions. However, banking mergers may not always be successful in their implementation, potentially harming customers. First, this article's problem formulation is procedures and regulations regarding limited liability company mergers in the banking business sector. And secondly, legal protection for customers after implementing a company merger in Indonesia. The research method in this article is legal research, with a statutory and regulatory approach and a conceptual approach. As for the results of this article, procedures and regulations regarding limited liability company mergers in the banking business sector are regulated in the Perseroan Terbatas Law, PP 28/1999, and OJK Regulation Number 6/POJK.07/2022. Legal protection for customers after a banking company merger in Indonesia is regulated in the provisions of PP 28/1999, OJK Regulation Number 41/POJK.03/2019, and OJK Regulation Number 6/POJK.07/2022. These provisions contain the legal ratio that bank merger efforts must consider customers' interests and not cause customer losses. Customers are also given alternative options for making objections or taking legal action if they feel disadvantaged and object to the company merger. Thus, what causes customer losses is actually at the implementation level, namely the legal structure (company organs and bank employees) that does not implement the provisions as regulated and the legal culture of society that does not understand the consequences of banking company mergers.